Origin and biogeographical history of Palaeotropical Piper (Piperaceae): multiple long-distance dispersals from South America initiated during the Middle Eocene climatic optimum - Metschina, Dominik; Cauz-Santos, Luiz A; Christenhusz, Maarten J M; Byng, James W; Suwanphakdee, Chalermpol; Smith, James F; Kahandawala, Imalka M; Gopallawa, Bhathiya; Wimalarathna, Nilni A; Wickramasuriya, Anushka M; Barfuss, Michael H J; Weiss-Schneeweiss, Hanna; et al. (Botanical journal of the Linnean Society, 2025)
Piper is the largest genus of Piperaceae and second largest in the angiosperms, but the biogeography and timing of its global radiation has not yet been fully investigated. Here, we carried out phylogenetic analyses with a molecular clock to provide a framework to examine divergence times and global biogeography and dispersal patterns of the genus, with a focus on Palaeotropical groups. Target enrichment produced 269 genes for 122 samples of Piperaceae. For Piper, we included species representing all geographic regions, most subgenera/sections, and all clades previously identified in phylogenetic studies. We used maximum likelihood (RAxML, IQ-Tree) and coalescent (ASTRAL-III) analyses to produce phylogenetic trees for Piperaceae. We optimized branch lengths for the coalescent species tree and provided divergence time estimates using treePL calibrated with a Cretaceous fossil of P. margaritae Martínez-A. and a maximum divergence age of 90.8 Myr, derived from a previous estimate of Piperaceae crown age. BioGeoBEARS was used for the biogeographic analyses. Target enrichment produced a generally well-supported maximum likelihood tree in which there was good support for (Verhuellia ((Manekia + Zippelia) + (Piper + Peperomia))). Intercontinental dispersals of Piper from South America started during the Middle Eocene climatic optimum (c. 40 Ma), first to southern Africa and the Pacific islands, followed by New Guinea, Southeast Asia, and the Philippines. In Asia, Piper dispersed and diversified across the Wallace and Lydekker’s lines multiple times. Despite there being only four endemic species, mainland Africa was colonized twice, and it appears the genus never diversified there.